COST ANALYSIS OF DESIGNING ERGONOMIC CINEMA CHAIR PRODUCTS WITH RFID USING THE CRITICAL PATH METHOD - Rossi Septy Wahyuni; Harda Winari Putri; Mei Raharja (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study discusses one of the cinemas in the city of Depok, West Java where the object of research is cinema seats. Adding RFID (Radio Frequency Identification), so you don't know the cost budget and time to accelerate project completion using the CPM method to solve problems. CPM (Critical Path Method) is an analytical technique for planning, scheduling and project control using the critical path method with a single estimate for the duration of an activity. The results of the study using the CPM method produced a budget of IDR 2,580,000 million for normal costs using normal time, while for costs that were accelerated by carrying out the analysis phase to speed up project time, it was IDR 2,890,000 million. The results of the CPM method for accelerating project time explain that activity A is preparation for preparing tools and materials. Activity B is making a foam pattern consisting of a seat, back, and armrests. Activity C is making patterns on oscar velvet which consists of seats, backs, and armrests. Activity D is foam cutting which consists of a seat, back, and armrests. Activity E is cutting Oscar's velvet fabric which consists of a seat, backrest, and armrests. Activity F installation of plastic shells for seat, backrest and arms. Activity G installation of seats, backrests, and armrests using hinge gears. Activity H RFID Installation. Activity I trial RFID. Activity J is the installation of chairs onto black powder coating iron. produces a normal time of 74 minutes, while for an accelerated time it can be 69 minutes by doing the compressing stage.